Young Shadow - Sears, Ben (Sears, Ben. Double+ adventure., 2021)
"Young Shadow usually protects sci-fi Bolt City by making deliveries for the food bank and rescuing pets. But one night, he discovers the Sludge Team, a conspiracy composed of a CEO of a chemical plant, trust-fund punks, and suspicious cops. To stop their evil plan, Young Shadow must don a couple of batons, knee pads, and a small black mask, and team up with Spiral Scratch - another benevolent protector in the fight - and metal-clad nuns. Drawn in bold yellows and blacks, this is a socially conscious action/adventure kid superhero tale. Full-color illustrations throughout."--Provided by publisher.